PERENCANAAN METODE PEMELIHARAAN PERKERASAN FLEXIBEL DENGAN ANALISA PAVEMENT CONDITION INDEX - Syahrul Hafid Amrulloh; Supriadi; Vivi Rahmawati (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
In analyzing the damage to the connecting platform, you can plan the Pavement Condition Index (PCI) method to determine the level of damage that has occurred and can be used as a reference in maintenance efforts. Pavement maintenance uses guidelines from the Director General of Civil Aviation Regulation Number: KP 94 of 2015 concerning Operational Technical Guidelines for Civil Aviation Safety Regulations. In analyzing the pavement damage on the link strip SP2 using the Pavement Condition Index method, after the results of the analysis are obtained, the type of repair will be determined according to the results of the analysis.